MULTICULTURAL EDUCATION AND TECHNOLOGY EDUCATION: INDEPENDENT MOVEMENTS ON PARALLEL PATHS - Gina Zanolini Morrison; Connie S. Hankee (Celt: A Journal of Culture, English Language Teaching & Literature, 2010)
Over the lastfew decades, two majorforces affecting the lives of second language learners have emerged in educational systems throughout the world: the increasing diversity of student populations and emerging technological advancements. The juxtaposition of these two phenomena presents an opportunity to bring together two educational movements: multicultural education and technology education. These entities are examined as parallel social movements whose convergence would provide the momentum for needed changes in today's educational systems.Banks, J. A. "Multicultural Education: Characteristics and Goals". In Multicultural Education: Issues and Perspectives (7thed.). Edited by Banks, J. A. &Banks, C.A. M., Hoboken,NJ: Wiley,2010.